Clozapine discontinuation in early schizophrenia: a retrospective case note review of patients under an early intervention service. Issue 1 (January 2018) - Shaker, Andrew; Jones, Rowena
Aim: Research in patients with treatment-resistant schizophrenia has demonstrated that clozapine discontinuation is associated with poor outcomes. There is, however, a paucity of research investigating the impact of clozapine discontinuation specifically in younger patients with more recent onset schizophrenia. A case note review was therefore conducted to ascertain medium-term prognoses in patients with treatment-resistant schizophrenia under an early intervention service (EIS) following clozapine discontinuation. Methods: The case notes of 25 patients under the care of Birmingham EIS who discontinued clozapine were examined retrospectively. Reasons for discontinuation were recorded. Clinical outcomes including total duration of inpatient or home treatment admission, antipsychotic dose, number of alternative antipsychotics prescribed and adverse events were recorded for both the year before and the year after stopping clozapine. Statistical comparisons of pre- and post-discontinuation clinical outcomes determined whether discontinuation had negative effects. Results: There was no significant difference between the pre- and post-discontinuation clinical status following clozapine discontinuation. More than half (56%) of patients remained stable after stopping clozapine. Mean inpatient or home treatment stay rose from 29.7 to 62.6 days ( p = 0.155), total antipsychotic dose from 50.1% of British National Formulary (BNF) limits to 60.5% ( p = 0.627), number of alternative antipsychotics prescribed from 1.28 to 1.80 ( p = 0.186), number of hospital/home treatment episodes from 0.20 to 0.44 ( p = 0.083) and number of adverse events from 0 to 0.20 ( p = 0.059). Non-compliance was the main reason for discontinuation (44%, n = 11). Conclusions: This is the first clozapine discontinuation study specifically considering EIS patients. Discontinuation did not lead to significant effects on 1 year outcomes, though the study is underpowered. These findings may be used to inform future prospective cohort discontinuation studies.